Italian feminism, workerism and autonomy in the 1970s - Patrick Cuninghame (Amnis)
This essay discusses some of the differences between Italian workerist feminism and liberal, socialist and separatist feminisms during the 1970s. It outlines the emergence of the main workerist feminist organizations around the issues of unpaid reproductive labour and of physical and sexual violence against women. The problems linked to relations between feminism and the anti-capitalist Autonomia social movement are also explored.